2008
DOI: 10.1063/1.2980383
|View full text |Cite
|
Sign up to set email alerts
|

A containerless levitation setup for liquid processing in a superconducting magnet

Abstract: Containerless processing of materials is considered beneficial for obtaining high quality products due to the elimination of the detrimental effects coming from the contact with container walls. Many containerless processing methods are realized by levitation techniques. This paper describes a containerless levitation setup that utilized the magnetization force generated in a gradient magnetic field. It comprises a levitation unit, a temperature control unit, and a real-time observation unit. Known volume of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
0
23
0
2
Order By: Relevance
“…Figure 4 shows the distribution of the gravitational force and Lorentz force of an object inside this superconducting magnet. Using such a magnet, Yin et al [11] showed that high-quality lysozyme crystals could be grown in container-less conditions [44]. They found that the orientation of multiple crystals occurred when they used different paramagnetic salts (CoCl 2 and NiCl 2 ) as precipitants at different concentrations [39].…”
Section: Magnet Systems That Provide a Strong And Stable Magnetic mentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 4 shows the distribution of the gravitational force and Lorentz force of an object inside this superconducting magnet. Using such a magnet, Yin et al [11] showed that high-quality lysozyme crystals could be grown in container-less conditions [44]. They found that the orientation of multiple crystals occurred when they used different paramagnetic salts (CoCl 2 and NiCl 2 ) as precipitants at different concentrations [39].…”
Section: Magnet Systems That Provide a Strong And Stable Magnetic mentioning
confidence: 99%
“…This simple glass vessel evolved into an integrative device equipped with a real-time observation apparatus [49], a temperature control system [44], and an auxiliary instrument. Sazaki et al and Yanagiya et al [49,50] designed a real-time observation device for use in a strong magnetic field by conveniently adjusting the sample location, as shown in Figure 6.…”
Section: Apparatuses For Protein Crystal Growth Inside a Magnetic mentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is difficult to carry out spaceflight-induced mutagenesis extensively owing to the limitations of high cost and few chances to board spaceships. Therefore, ground-based simulated experiments have greater practical significance, and high-magnetogravity experiments are a good choice to simulate the space environment (16).…”
mentioning
confidence: 99%